Conscious State Assessment in Emergency Ambulance Calls in Western Australia - Belcher, Jason Laurence (Curtin University, 2023)
A key component of prioritising emergency ambulance calls is the patient’s level of consciousness, however little is known about how accurately this can be determined in telephone triage. My research addressed this question using data from St John Ambulance. While I found that altered conscious states are a good predictor of patient acuity, there are significant challenges in assessing it accurately during emergency calls, and I proposed strategies to better assess conscious states in telephone triage.